2009
DOI: 10.2355/isijinternational.49.1156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anisotropy on Dendritic Growth in Binary Alloy with Phase–Field Simulation

Abstract: Some computational results on dendritic growth in binary alloy are obtained by using a phase-field model coupled the solute gradient term. The effect of crystalline anisotropy on the morphological formation, tip steady state and the solute partition is investigated for different dendrites. The interface formation and tip steady state are affected evidently with increase in anisotropy for ͗100͘ dendrite growth, but the solute partition coefficient is not significantly influenced. For ͗110͘ preferred growth dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Such a discontinuous change in V tip at d % d c has also been reported previously in the case of CPFM simulations for solidification of binary alloys. Kim and Kim [23] reported a sudden drop in V tip , whereas Xiao et al [24] reported an abrupt increase in V tip , similar to that observed in the present study.…”
Section: Effect Of Interfacial Energy Anisotropy On Dendritic Growthsupporting
confidence: 90%
See 2 more Smart Citations
“…Such a discontinuous change in V tip at d % d c has also been reported previously in the case of CPFM simulations for solidification of binary alloys. Kim and Kim [23] reported a sudden drop in V tip , whereas Xiao et al [24] reported an abrupt increase in V tip , similar to that observed in the present study.…”
Section: Effect Of Interfacial Energy Anisotropy On Dendritic Growthsupporting
confidence: 90%
“…Mullis [25] reported that in the case of d < d c , CPFM results in an anomalous behavior of dendritic growth in a pure undercooled melt: the steady-state tip radius of dendrites exhibits a minimum with increasing melt undercooling, which is contradictory to the scaling laws predicted by dendritic growth theories [26][27][28][29][30][31][32][33]. Moreover, recent reports on CPFM simulations showed that the dendrite tip velocity changed discontinuously with the interfacial energy anisotropy crossing the critical value [23,24]. Since the dendritic pattern is formed by an interplay between the interfacial energy anisotropy and growth kinetics through an interfacial process and long-range transport, it is of fundamental interest to know how ECHM differs from CPFM in simulating the dendrite tip operation during solidification.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It can be seen that, the side-branches are highly developed at low , but these features are attributed to the effect of crystalline anisotropy. 16 But it should be noted that the coalescence of the side arms is observed with the increasing of kinetics coefficient, and the realistic growth patterns are obtained including the sector form and plate; however, the symmetry of dendrite morphology is not disrupted. So, the symmetry of formation is crucially determined by the anisotropy for 110 dendrites growth without flow.…”
Section: Effect Of Growth Kinetics On 110mentioning
confidence: 96%
“…So, the symmetry of formation is crucially determined by the anisotropy for 110 dendrites growth without flow. 16 Furthermore, every structure of the crystal growth has its ridges due to the extremely high local solidification rate that occurs to eliminate negative curvature, and the thickness of the ridges become narrow with the increment of .…”
Section: Effect Of Growth Kinetics On 110mentioning
confidence: 99%